MAKASSAR GOVERNMENT POLICY IN INVOLVING STUDENTS IN THE FREE EDUCATION PROGRAM - Kurniati, Poni Sukaesih; Rattealo, Monalisa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research discusses the Makassar government’s policy involving students in the free education program. This research itself aims to find out the truth by analyzing the implementation of Makassar government policies in involving students in free education programs, finding out the benefits obtained from the implementation and the challenges faced in implementing this policy. This research method is a systematic literature review by collecting data through internet searches on relevant government policy reviews, such as government officials, educational institutions, and students involved in this program. The results show that the Makassar government’s policy in involving students in the free education program has been implemented well. Students involved as teaching staff make a positive contribution in improving the quality of learning and providing motivation to students. This program also succeeded in increasing the accessibility of education for people in need. This program is also expected to have a positive impact on society, government and students. The free education program has had a huge impact on the world of education, children who previously could not go to school because they were economically disadvantaged can receive an education where they are future candidates for the nation